The impact of pathological factors on the structure and function of erythrocyte membranes: from the molecular level to clinical consequences - D.А. Liadov (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Red blood cells play a key role in gas transport and tissue oxygenation. Pathological alterations in the structure and function of erythrocyte membranes lead to impaired deformability, reduced ability to traverse microvessels, and microcirculatory failure. Oxidative stress, lipid peroxidation, and changes in membrane lipid composition significantly affect oxygen delivery, contribute to chronic hypoxia, and exacerbate systemic diseases, including cardiovascular, neurodegenerative disorders, and complications of infectious diseases, notably COVID-19.